Amine-Terminated Silver Nanoparticles Exhibit Potential for Selective Targeting of Triple-Negative Breast Cancer - Jayshree H. Ahire; Qi Wang; Yuewei Tao; Yimin Chao; Yongping Bao (Applied Nano)
Silver nanoparticles (AgNPs) demonstrate potential in treating aggressive cancers such as triple-negative breast cancer (TNBC) in preclinical models. To further the development of AgNP-based therapeutics for clinical use, it is essential to clearly define the specific physicochemical characteristics of the nanoparticles and connect these properties to biological outcomes. This study addresses this knowledge gap through detailed investigations into the structural and surface functional relationships, exploring the mechanisms, safety, and efficacy of AgNPs in targeting TNBC. The surface functionality of nanoparticles is crucial not only for their internalization into cancer cells but also for enhancing their toxicity toward tumor cells. Although the nanoparticles internalized into cancer cells, they failed to exhibit their full toxicity against the cancer. Herein we report a solvent-assisted synthesis amine, mercaptohexanol and bifunctional silver nanoparticles and performing comparative study to understand their selectivity and toxicity toward TNBC cells. The nanoparticles are fully characterized by UV–visible absorption spectroscopy, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), and dynamic light scattering measurement (DLS). The synthesis method achieves an extremely high yield and surface coating ratio of synthesized colloidal AgNPs. Our findings reveal that the amine-capped AgNPs exhibit significant selective toxicity against TNBC cell lines MCF7 and MDA-MB-231 at a concentration of 40 µg/mL without affecting normal breast cell lines MCF10A. This study underscores the potential of functionalized AgNPs in developing safe and targeted therapeutic approaches for treating aggressive cancers like TNBC, laying the groundwork for future clinical advancements.